2006
DOI: 10.1593/neo.05754
|View full text |Cite
|
Sign up to set email alerts
|

Whole Transcriptome Amplification for Gene Expression Profiling and Development of Molecular Archives

Abstract: Expression profiling of clinically obtainable tumor specimens has been hindered by the need for microgram quantities of RNA. In vitro transcription (IVT)-based amplifications are most commonly used to amplify small quantities of RNA for microarray analysis. However, significant drawbacks exist with IVT-based amplification, and the need for alternative amplification methods remains. Herein, we validate whole transcriptome amplification (WTA), an exponential amplification technique that produces cDNA libraries a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 26 publications
5
32
0
Order By: Relevance
“…Our study is in agreement with Tomlins et al, 17 who have recently reported promising global gene expression data from FFPE CaP specimens.…”
Section: Discussionsupporting
confidence: 93%
“…Our study is in agreement with Tomlins et al, 17 who have recently reported promising global gene expression data from FFPE CaP specimens.…”
Section: Discussionsupporting
confidence: 93%
“…Isolation of RNA from urine and TransPlex whole transcriptome amplification (WTA) were as described (12). Quantitative PCR (qPCR) was used to detect seven prostate cancer biomarkers (AMACR, ERG, GOLPH2, PCA3, SPINK1, TFF3, and TMPRSS2:ERG) and the control transcripts PSA and GAPDH from WTA-amplified cDNA essentially as described (12,13 fusion-positive or fusion-negative status observed in tissue samples (8,17), with positive samples defined as those with C t values of <37. As PCA3 has been reported to be a prostate tissue-specific marker (7), it was normalized against urine PSA (C tPSA À C tPCA3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Here state of the art techniques in RNA amplification were employed using MTOPS clinical samples in order to perform expression array analysis on 30K cDNA arrays. 48,49 These approaches were previously successful with prostate cancer samples. 49 As part of this pilot study, 30 frozen tissue samples that originated from needle biopsies of the left or right transitional zone of the prostatic gland (n=15 each) were obtained.…”
Section: Development Of a Molecular Signature For Bph Responsive To 5mentioning
confidence: 99%
“…48,49 These approaches were previously successful with prostate cancer samples. 49 As part of this pilot study, 30 frozen tissue samples that originated from needle biopsies of the left or right transitional zone of the prostatic gland (n=15 each) were obtained. Each of these MTOPS specimens represented a single case and all samples were from nonrandomized patients.…”
Section: Development Of a Molecular Signature For Bph Responsive To 5mentioning
confidence: 99%
See 1 more Smart Citation